Booking for trouble - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries., 2026)
It's all hands on deck when a dead body is found near the small town of Briar Creek in this Library Lover's Mystery from the New York Times bestselling author of A Merry Little Murder Plot. Just off the shores of the coastal Connecticut town of Briar Creek are two small islands, which library director Lindsey Norris visits with her new book-boat, inspired by the bookmobiles she's seen traveling across the country. Nothing, not even the infamous feud between the families who own the Split Islands, can stop Lindsey from getting books into the hands of readers. But when Lindsey and her boat captain husband, Mike Sullivan, discover a body on the rocky outcropping of one of the islands, Lindsey's new library venture quickly becomes a murder investigation. At news of the crime, hostilities between the two families are reignited. Long buried secrets are revealed, tensions spark, and suspects abound. As Lindsey navigates treacherous waters (both literal and metaphorical), she must use her research skills and community ties to solve the murder and bring peace to the islands before her book-boat dreams are sunk.